(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2024)
The article presents the results of extension experiences at the National University of Luján, aimed at addressing the lack of tools for environmental information management in local public spheres, and the consequent limitations in the usability of the knowledge produced for decision-making in the case of Municipality of Luján. To this end, the design and operation of the Luján Integrated Environmental Information System (SIAI) is described, from its beginnings within the framework of the Integrated Local Sustainable Development Projects Program (Dpto. Cs. Sociales - UNLu) to the present day. The aim is to present reflections on the extension experiences carried out and in progress (2019-2022 and 2023-2025) and to outline their course of action based on their articulation with a research project aimed at integrating AI and natural language model-based functionalities into the SIAI. Finally, the tool’s consolidated, pending and projected achievements are reviewed.